The trial of Gustav Rau, Otto Monsson, and Willem Smith : the "Veronica" trial - Keeton, George W.; Cameron, John; Great Britain. High Court of Justice. King's Bench Division (London : W. Hodge, 1952)
Tried in King's Bench Division, High Court of Justice, at the Liverpool assizes, May 1-14, 1903, for the murder of Alexander Shaw captain of the "Veronica", on Dec.14, 1902 and for the piracy in seizing the ship. The matter was reported to the British authorities by the captain of the S.S. Brunswick.
Gustav Rau's real name is August Mailahn (p.167)
Tried in the King's Bench Division, High Court of Justice, at the Liverpool assizes, May 12-14, 1903, for the murder of Alexander Shaw on Dec. 14, 1902.
The matter was reported to the British authorities by the captain of the S.S. Brunswick.
Keywords: Trials (Mutiny) -- England